HUKUM ISLAM DAN TRANSFORMASI SOSIAL MASYARAKAT JAHILIYYAH: (Studi Historis Tentang Karakter Egaliter Hukum Islam) - Amin, Abd. Rahim (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2012)
This paper describes the problem of Islamic Law and Social Transformation Society of Ignorance. Through discussion with the understanding that the historical approach is obtained with a legal background pre-Islamic Jahiliyyah racist, feudal and patriarchal, Islam was born and brought up with legal changes to the character as opposed to the laws of Jahiliyyah. Islam teaches equality is reflected in the principles and laws of Allah and the Prophet Muhammad and his followers who want the egalitarian life. Conflicts of Quraish against Islam is closely linked to the religious aspect and the social aspect is a counter to the egalitarian system of Islamic law. by implication, an understanding of Islamic law must be followed by the realization that Islamic law has egalitarian character and it is a social change of the law that are not egalitarian Jahiliyyah into an egalitarian Islamic law.